2019
DOI: 10.5713/ajas.18.0743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on body temperature, milk production, and reproduction in dairy cows: a novel idea for monitoring and evaluation of heat stress — A review

Abstract: Heat stress exerts a substantial effect on dairy production. The temperature and humidity index (THI) is widely used to assess heat stress in dairy operations. Herein, we review the effects of high temperature and humidity on body temperature, feed intake, milk production, follicle development, estrous behavior, and pregnancy in dairy cows. Analyses of the effects of THI on dairy production have shown that body temperature is an important physiological parameter in the evaluation of the health state of dairy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 49 publications
3
105
0
3
Order By: Relevance
“…Temperature-Humidity Index (THI) is a widely accepted criterion of heat stress measurement, while generally cows experience heat stress at 25 • C. However, recently researchers are focusing THI calculation at the most ambient level, considering the actual micro-climates around cows. This approach of THI evaluation, combined with the physiological parameters of heat stress, is essential to depict the actual heat stress magnitude of cows [114]. By this way, managers can monitor heat stress events and design appropriate housing and husbandry to attain heat stress abatement through appropriate cooling, management, and nutrition support aids [110].…”
Section: Mitigation Strategies Towards Heat Stress and Its Consequencesmentioning
confidence: 99%
“…Temperature-Humidity Index (THI) is a widely accepted criterion of heat stress measurement, while generally cows experience heat stress at 25 • C. However, recently researchers are focusing THI calculation at the most ambient level, considering the actual micro-climates around cows. This approach of THI evaluation, combined with the physiological parameters of heat stress, is essential to depict the actual heat stress magnitude of cows [114]. By this way, managers can monitor heat stress events and design appropriate housing and husbandry to attain heat stress abatement through appropriate cooling, management, and nutrition support aids [110].…”
Section: Mitigation Strategies Towards Heat Stress and Its Consequencesmentioning
confidence: 99%
“…Morignat et al (2015) reported that each degree temperature increase above a certain threshold is associated with a 5% increase in mortality risk. Heat stress adversely affects follicle development and reduces pregnancy rate in cattle (Liu et al, 2019). An increase in temperature-humidity index from 72 to 78 reduced pregnancy rate from 39.4 to 31.6% in dairy cows (Domínguez et al, 2005).…”
Section: Productive and Reproductive Performance Of Livestockmentioning
confidence: 99%
“…Even though swine milk is not a primary product for human consumption, quality and yield of milk in lactating sows plays an important role for feeding viable offspring raised for meat. Several previous reports suggested a potential direct correlation between environmental temperature and milk yield (Black et al, 1993;West, 2003;Liu J. et al, 2019). Heat-stressed lactating sows reduce their feed intake and their declined milk production does negatively affect piglet growth and development during lactation.…”
Section: Swine -Meatmentioning
confidence: 99%